2018
DOI: 10.1111/1758-2229.12663
|View full text |Cite
|
Sign up to set email alerts
|

The pH regulator PacC: a host‐dependent virulence factor in Botrytis cinerea

Abstract: The phytopathogenic fungus Botrytis cinerea is able to infect a wide variety of plants and plant tissues with differing chemical compositions. During its interaction with the host, this pathogen modulates its ambient pH by secreting acids or ammonia. In this work, we examined the Pal/Pac pathway, the fungal ambient pH-responsive signalling circuit, and investigated the role of the PacC transcription factor. Characterization of the BcpacC deletion mutant revealed an alteration of both fungal growth and virulenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 55 publications
0
46
0
Order By: Relevance
“…Botrytis cinerea produces phytotoxic compounds, such as botrydial and botcinolides, as well as cell‐wall‐degrading enzymes . B. cinerea like other postharvest pathogens modulate the host pH environment during infection, and low pH is conducive to gray mold development . Botrytis cinerea secretes a number of organic acids, of which citric acid appears to play an important role in its interaction with host plant tissue .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Botrytis cinerea produces phytotoxic compounds, such as botrydial and botcinolides, as well as cell‐wall‐degrading enzymes . B. cinerea like other postharvest pathogens modulate the host pH environment during infection, and low pH is conducive to gray mold development . Botrytis cinerea secretes a number of organic acids, of which citric acid appears to play an important role in its interaction with host plant tissue .…”
Section: Discussionmentioning
confidence: 99%
“…Botrytis cinerea secretes a number of organic acids, of which citric acid appears to play an important role in its interaction with host plant tissue . Oxalic acid, another organic acid that is implicated in virulence in Sclerotinia sclerotiorum , a close relative to B. cinerea , does not appear to be involved in the gray mold‐apple interaction …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using mutant strains carrying the Δ pac-3 (or rim101 / pacC ) revealed that the PAC-3 transcription factor correlates with fungal traits beyond pH signaling, impacting fundamental biological processes, including cell morphology, hyphae growth, conidiation, and adaptation to the host or nutritional variances ( Ferreira-Nozawa et al , 2006 ; Mendes et al , 2012 ; O'Meara et al , 2014 ; Martins et al , 2018 , 2019 ; Rascle et al , 2018 ). In Neurospora crassa , the deletion of pac-3 and the pal cascade-associated genes, except for Δ pal-9 / palI, diminished aerial growth, reduced conidiation, and resulted in high production of melanin, in comparison with that in the wild-type strain ( Virgilio et al , 2016 ).…”
Section: Introductionmentioning
confidence: 99%